Clinical and Mycological Profiling of Superficial Mycoses from Tertiary Care Hospital in Nepal - Sapkota, Jyotshna; Bhusal, Mohan; Aryal, Sachin K.; Khadka, Shusila; Pandey, Ritu; Khanal, Laxmi Kant; Adhikari, Ram Prasad (Nepal Medical College Journal, 2025)
Superficial mycoses are among the most common fungal infections worldwide, affecting the skin, hair and nails. Their prevalence and clinical profile can vary based on geographic, environmental, and host factors. This study aimed to determine the clinical and mycological profile of superficial mycoses among patients attending a tertiary care hospital. A cross-sectional study was conducted among 140 clinically diagnosed cases of superficial mycoses at Nepal Medical College Teaching Hospital. Detailed demographic and clinical data were recorded. Samples including skin scrapings, nail clippings, and plucked hairs were collected and subjected to direct KOH microscopy and fungal culture on Sabouraud dextrose agar and dermatophyte testing agar (DTM). Fungal isolates were identified based on colony morphology, lactophenol cotton blue mount and standard biochemical tests. Among 140 patients, 72 (51.42%) were male and 68 (48.58%) were female (male-to-female ratio 1.06:1). The most affected age group was 31– 40 years (27.86%). The most common clinical diagnoses were onychomycosis and Tinea corporis (24.28% each), followed by Tinea manuuam (14.29%). KOH microscopy was positive in 25.71% and culture in 15.71% of cases. Trichophyton spp. was the most frequently isolated fungus (54.54%), followed by Epidermophyton spp. (13.64%). Non-dermatophyte fungi such as Candida spp., Rhizopus spp., and Penicillium spp. were also identified. Superficial mycoses are common and often chronic, with varied clinical presentations. Trichophyton remains the predominant etiological agent, but non-dermatophyte fungi are emerging. Early diagnosis, accurate species identification, and appropriate treatment are essential to reduce disease burden and prevent recurrence.